ANALISIS KEBUTUHAN PENGEMBANGAN BOOKLET BERMUATAN KEARIFAN LOKAL SEBAGAI MEDIA PEMBELAJARAN MATERI KEANEKARAGAMAN HAYATI PADA FASE E KELAS X SMA/MA - Atharia Maulina, Fadila; Razak, Abdul (Universitas Cokroaminoto Palopo, 2024)
Learning is a process of interaction between students and teachers for the purpose of students gaining knowledge. This research focuses on the definition of development research using the 4D model. one of the steps of the define stage is student analysis. The analysis was carried out during the observation process on the research subjects, namely the biology teacher and 30 students in class X Phase E of SMA Negeri 5 Pariaman. The research methods used included distributing questionnaires to 30 students and conducting interviews with a biology teacher, with qualitative data collected which was analyzed using descriptive analysis. This research focuses on the definition of development research using the 4-D model. The research methods used included distributing questionnaires to 30 students and conducting interviews with a biology teacher, with qualitative data collected which was analyzed using descriptive analysis. Based on the research that has been carried out, it is concluded that biodiversity material is material that is difficult for students to understand, this is because there is too much material and there are confusing terms.